Fresno County Bar Association Law Day Luncheon with U.S. Attorney David Levy at Fresno Hilton Ballroom - Watkins, Howard::::::::: (1988)
Fresno Mayor Dale Doig presenting a City of Fresno Law Day Proclamation to Fresno County Bar Association President Herbert Levy